Effects of Exogenous Abscisic Acid on the Physiological and Biochemical Responses of Camellia oleifera Seedlings under Drought Stress - Dayu Yang; Yongzhong Chen; Rui Wang; Yimin He; Xiaofan Ma; Jiancai Shen; Zhilong He; Hanggui Lai (Plants, 2024)
This study comprehensively investigates the physiological and molecular regulatory mechanisms of Camellia oleifera seedlings under drought stress with a soil moisture content of about 30%, where exogenous abscisic acid (ABA) was applied via foliar spraying at concentrations of 50 µg/L, 100 µg/L, and 200 µg/L. The results demonstrated that appropriate concentrations of ABA treatment can regulate the physiological state of the seedlings through multiple pathways, including photosynthesis, oxidative stress response, and osmotic balance, thereby aiding in the restructuring of their drought response strategy. ABA treatment effectively activated the antioxidant system by reducing stomatal conductance and moderately inhibiting the photosynthetic rate, thus alleviating oxidative damage caused by drought stress. Additionally, ABA treatment promoted the synthesis of osmotic regulators such as proline, maintaining cellular turgor stability and enhancing the plant’s drought adaptability. The real-time quantitative PCR results of related genes indicated that ABA treatment enhanced the plant’s response to the ABA signaling pathway and improved disease resistance by regulating the expression of related genes, while also enhancing membrane lipid stability. A comprehensive evaluation using a membership function approach suggested that 50 µg/L ABA treatment may be the most-effective in mitigating drought effects in practical applications, followed by 100 µg/L ABA. The application of 50 µg/L ABA for 7 h induced significant changes in various biochemical parameters, compared to a foliar water spray. Notably, superoxide dismutase activity increased by 17.94%, peroxidase activity by 30.27%, glutathione content by 12.41%, and proline levels by 25.76%. The content of soluble sugars and soluble proteins rose by 14.79% and 87.95%, respectively. Additionally, there was a significant decrease of 31.15% in the malondialdehyde levels.